Compressive Behavior of Slender Circular Columns with Double GFRP Spirals and Bars - Awera, Yousef Ayman (2021)
A Master of Science thesis in Civil Engineering by Yousef Ayman Awera entitled, “Compressive Behavior of Slender Circular Columns with Double GFRP Spirals and Bars”, submitted in April 2021. Thesis advisor is Dr. Mohammad AlHamaydeh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).